How High Can You Climb? Earnings Inequality and Intragenerational Earnings Mobility in a Developing Country: Evidence from Thai Tax Returns - Athiphat Muthitacharoen; Trongwut Burong (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates inequality and intragenerational economic mobility in a developing country with large inequality. Understanding economic mobility is important because it shapes our perception of inequality. Despite its significance, evidence on intragenerational mobility, especially that based on administrative data, is relatively limited in developing countries. Using Thailand's tax return data, we study the evolution of earnings inequality, estimate medium-term earnings mobility, and examine the heterogeneity of mobility across age, gender and employment arrangement. Our analysis yields three main findings. First, annual earnings inequality rises during the 2009-2018 period. We find that the inequality is largely permanent, and its increase is primarily driven by top-earnings workers. Second, we find that medium-term mobility follows a U-shaped pattern across the earnings distribution, with extremely high persistence at the top. Our suggestive comparison indicates that Thailand's earnings mobility is among the lowest in the pool of evidence from both developed and developing countries. Third, there is a considerable heterogeneity in mobility regarding employment arrangement. Workers in less-formal jobs have much lower upward mobility than those in more-formal employment. Our findings also indicate significant heterogeneity in mobility with respect to gender and age. These findings highlight the importance of ensuring that any increase in inequality caused by the Covid-19 crisis does not become permanent, as well as improving access to opportunities for vulnerable workers.
Keywords: D31; D63; H20; J31; J60; 330; intragenerational earnings mobility; inequality